DINAMIKA KELEMBAGAAN PENGELOLAAN AIR IRIGASI - RACHMAN, BENNY; KARIYASA, KETUT (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 1 Februari 2003, 2012)
The increasing demand of water for economic activities trigger a consequence of higher pressure of irrigation water needs. On the other side, Water User’s Association (P3A), an organization managing irrigation water from tertiary and quarter channel up to the rice field, finds it difficult to manage water resource in perspective of quantity, times and place. In line with that, institutional adjustment in both government institution and institution at farm level should be carried out in order to improve efficiency of water management. Furthermore, to support local autonomy and the empowerment of Water Users Assosiation to undertake larger responsibility in irrigation management as a strategic approach to improve efficiency of irrigation system management at the local level. The involvement of farmers in managing irrigation water distribution should be promoted up to the upper level, i.e. through the development of P3A federation based on hidrological spread i.e. irrigation area.
Keywords: Institutional, P3A Federation, Autonomy